566Ear infection trajectories and academic, behavioural and quality of life outcomes: A population-based longitudinal study. (2nd September 2021) - Wang, Jing; Quach, Jon; Sung, Valerie; Carew, Peter; Wake, Melissa
Abstract: Background: Middle ear infection is a common disease in childhood. Outcomes might vary by its patterns and persistence over time. We aimed to investigate 1) typical trajectories of ear infections throughout childhood and 2) their associations with child outcomes. Methods: Design & Participants: Two parallel cohorts assessed biennially from 2004 to 2014 spanning ages 0-1 to 10-11 years (B cohort, n = 3721) and ages 4-5 to 14-15 years (K cohort, n = 3489) in the Longitudinal Study of Australian Children. Ear infection: Parent-reported ongoing ear infections (B: waves 1-6; K: waves 1, 2, 4, 5). Outcomes (wave 6): National academic standardized test, teacher-reported learning, parent and teacher-reported behaviour and self-reported quality of life. Analysis: Latent class models identified ear infection trajectories. Linear regression quantified associations between trajectories and outcomes. Results: Four probability trajectories of ear infection emerged in both cohorts: "consistently low" (B 86.2%, K 87.0%), "moderate to low" (5.5%, 9.7%), "low to moderate" (7.0%, 1.5%), and "consistently high" (1.4%, 1.8%). In K cohort, the "consistently high" group had the worst outcomes (effect sizes 0.2-0.8 SDs), with effect sizes largest for psychosocial and language outcomes. "Moderate to low" and "low to moderate" groups showed no to marginal academic associations, but behaviour and quality of life were 0.2-0.3 SDs poorer than the "consistently low" group. Similar but attenuated associations were seen in B cohort. Conclusions: Sizable adverse outcomes followed the consistently high trajectory, suggesting cumulative rather than age-dependent burden. Additional information about comorbidities, predictors and objective presence of ear infections could inform causal relationships. Key messages: Parent-reported ear infections follow four childhood trajectories (consistently low, moderate to low, low to moderate, consistently high). Sizable adverse outcomes follow the consistently high trajectory.